2019
DOI: 10.7554/elife.51401
|View full text |Cite
|
Sign up to set email alerts
|

Movement of accessible plasma membrane cholesterol by the GRAMD1 lipid transfer protein complex

Abstract: Cholesterol is a major structural component of the plasma membrane (PM). The majority of PM cholesterol forms complexes with other PM lipids, making it inaccessible for intracellular transport. Transition of PM cholesterol between accessible and inaccessible pools maintains cellular homeostasis, but how cells monitor the accessibility of PM cholesterol remains unclear. We show that endoplasmic reticulum (ER)-anchored lipid transfer proteins, the GRAMD1s, sense and transport accessible PM cholesterol to the ER.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
180
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(193 citation statements)
references
References 103 publications
(150 reference statements)
12
180
0
1
Order By: Relevance
“…Unglycosylated sterols and glycosylated sterols (including steryl glycosides and acyl sterol glycosides) are integral components of the plant plasma membranes, especially in membrane microdomains (50, 74). The increase in host acyl-glycosylated phytosterols by DSF treatment shown in our targeted lipidomic analysis might be a consequence of direct sterol modifications – such as DSF being metabolized to a precursor of acyl source for steryl glucoside acyltransferase (75), or from a potential sterol exchange between PM and ER through PM-ER contact sites (76, 77) — both of which require further investigation. Through the modulation of sterols, DSF interferes with plant PTI through the alteration of both the clustering and endocytic internalization of the surface receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Unglycosylated sterols and glycosylated sterols (including steryl glycosides and acyl sterol glycosides) are integral components of the plant plasma membranes, especially in membrane microdomains (50, 74). The increase in host acyl-glycosylated phytosterols by DSF treatment shown in our targeted lipidomic analysis might be a consequence of direct sterol modifications – such as DSF being metabolized to a precursor of acyl source for steryl glucoside acyltransferase (75), or from a potential sterol exchange between PM and ER through PM-ER contact sites (76, 77) — both of which require further investigation. Through the modulation of sterols, DSF interferes with plant PTI through the alteration of both the clustering and endocytic internalization of the surface receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Their location in the very small spaces in contact sites may confer various advantages 68,71 . The active form of cholesterol is the substrate transported from the plasma membrane to the ER by the Aster/GRAMD1 complex 79,80 …”
Section: Intracellular Cholesterol Transportmentioning
confidence: 99%
“…The pathway between cholesterol removal from plasma membrane and its subsequent transport to the ER represents a field of extensive investigation aimed to identify specific transporters involved in the regulation of cholesterol homeostasis. Recent studies identified Aster/GRAMD1 as essential transporters of cholesterol into ER and regulating the cellular uptake of HDL-derived cholesterol ( Sandhu et al, 2018 ; Naito et al, 2019 ). ORP2 protein was also identified as a unique transporter of cholesterol from ER to the plasma membrane ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%